2018
DOI: 10.1371/journal.pone.0203920
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of femoral muscle from rats at different periods of time after death

Abstract: Clarification of postmortem metabolite changes can help characterize the process of biological degradation and facilitate investigations of forensic casework, especially in the estimation of postmortem interval (PMI). Metabolomics can provide information on the molecular profiles of tissues, which can aid in investigating postmortem metabolite changes. In this study, liquid chromatography-mass spectrometric (LC-MS) analysis was performed to identify the metabolic profiles of rat femoral muscle at ten periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Dopamine is a major transmitter in the extrapyramidal system of the brain and is important in regulating movement. A family of receptors (dopamine receptors) mediates action, which plays a major role in the reward-motivated behaviour 35 . The enrichment of the relative abundance of Phyla Bacteroidetes and genera Alistipes, unclassified Rikenellaceae might be related with biosynthesis of fatty acid and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is a major transmitter in the extrapyramidal system of the brain and is important in regulating movement. A family of receptors (dopamine receptors) mediates action, which plays a major role in the reward-motivated behaviour 35 . The enrichment of the relative abundance of Phyla Bacteroidetes and genera Alistipes, unclassified Rikenellaceae might be related with biosynthesis of fatty acid and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, metabolomics analysis can help not only in clarifying possible post-mortem (PM) changes within the tissue to improve the reliability of the interpretation of the results but also in forensics, cancer, and transplantation research. 28 To unveil metabolic markers correlated with the PMI, Du et al 29 performed an untargeted metabolomics analysis of femoral muscle from Sprague−Dawley rats based on both HILIC and RP-LC−MS/MS. The authors investigated the metabolic shifts from PMIs of 10 to 168 h, and they concluded that the greatest changes occurred after 48 h PM, highlighting 19 metabolites that could serve as possible indicators to increase accuracy when determining the time of death.…”
Section: ■ Sample Collection and Treatmentmentioning
confidence: 99%
“…Similarly, a comprehensive untargeted LC-MS-based metabolomics approach by Du et al investigated the metabolic profiles of rat femoral muscle over a 168 h PMI and using PLS-DA found changes of 59 features with strong associations to the PMI, predominantly within 48 h after death. Of these, 19 endogenous metabolites were positively identified using an in-house database and included, for example, also niacinamide (Du et al, 2018). However, data on the validation of proposed biomarkers in humans is sparse, due to the ethical constraints for controlled human studies.…”
Section: Determination Of the Post-mortem Intervalmentioning
confidence: 99%